Pengaruh Pengembangan Sumber Daya Manusia dan Disiplin Kerja terhadap Kinerja Pegawai (Studi pada Bagian Umum dan Hukum Tata Laksana Universitas Brawijaya) - Lusianita, Maria (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2021)
Employees in an agency need to be managed professionally in order to achieve a balance between the needs of employees and the guidance untill their capabilities of the agency. Organizations benefit from operational continuity with increased performance, while employees feel they have a greater commitment to the organization. In line with the phenomenon of human resource development, employee work discipline must also be developed. This study aims to explain the impact of human resource development and work discipline on non-PNS employees and employees. The results of the study state that the development of human resources on employee performance shows a positive but insignificant effect, besides that the effect of work discipline on employee performance shows a positive and significant effect. In addition, the moderating effects of age, work status, and years of service also do not have a significant effect.